The Role of Communication in Behavioral Freedom During the Coordination Process of An Organization - Pujiati, Pujiati (International Conference of Moslem Society, 2018)
Communication is the means to clarify expectations and to coordinate the tasks responsibility that allow the people to achieve the objectives of the organization to be more efficient and effective. Communication is the exchange of information between the sender and the receiver in which the process of information and the meaning of the message is delivered well. Most of the tasks responsibility that is done by a team works on interdependent and mutually connected to each other of the organization’s member. Therefore, the effectiveness of communication plays an important role in determining whether there is a profit or loss in the process of communication. An organization is a group of people who work in interdependence through communication. In organizational activity, there is the process of delivering and receiving the messages to run the organization’s performance. It means that the role of communication is very influential in behavioral freedom during the coordination process of an organization. This research deals with the notion of communication, communication function, model of communication, communication barriers, and how to improve the communication process. The purpose of this research was to know and to describe the role of communication in behavioral freedom during the coordination process of an organization. This research was a descriptive research. The results of this research showed that the development behavioral freedom during the coordination process of an organization needed to be dynamic during the working performance to achieve the goal; one of them was to understand and perform the communication process properly. Some of the obstacles in communication, according to Robbins and Judge, were the process of filtering, selective perception, information overload, emotions, language, silence, communication apprehension, gender differences, etc. Those obstacles could be solved by interpersonal communication, strategies and skills to communicate described in this paper, so that the organization could run well reaching the desired goal.